The The effect of health education on first aid for drowning victims on lifeguard knowledge in swimming pools in Jambi City: A Pre-Experimental Study on Knowledge Improvement Through Video-Based Intervention in Jambi City’s Aquatic Facilities - Subandi, Andi; Noerjoedianto, Dwi; Taqwa, Muhammad (Riset Informasi Kesehatan, 2025)
Background: Drowning is defined as death caused by asphyxia due to immersion in water that occurs within 24 hours of the incident. Immediate and appropriate first aid is essential to increase the chances of survival. Lifeguards, as the front line in aquatic emergencies, must have adequate knowledge and skills in performing first aid for drowning victims. Health education is one of the efforts to improve lifeguards' understanding and ability to act promptly and correctly in such critical situations. Method: This study employed a pre-experimental research design using a one-group pretest-posttest approach. A total of 33 lifeguards from three different swimming pools in Jambi City were selected using a total sampling technique. Data were collected through a structured questionnaire measuring the level of knowledge regarding first aid for drowning victims before and after the health education intervention. To determine the significance of the changes in knowledge, data were analyzed using the Wilcoxon signed-rank test. Results: The results of the bivariate analysis using the Wilcoxon test showed a Z value of -5.205 with a significance level of 0.001 (p < 0.05). These findings indicate a statistically significant improvement in lifeguards’ knowledge after receiving health education. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Conclusion: Health education has a significant positive effect on increasing lifeguard knowledge regarding first aid for drowning victims in Jambi City swimming pools. These results emphasize the importance of continuous education and training programs to enhance the readiness and effectiveness of lifeguards in responding to drowning emergencies.